Comparative analysis of RNA genomes of mouse hepatitis viruses. - Lai, M M (1981)
The RNA genomes of various murine hepatitis virus (MHV) strains were studied by T1-oligonucleotide fingerprinting analysis with regard to their structure and sequence relationship. It was found that the MHV particles contained only positive-stranded 60S RNA which had a "cap" structure at its 5' end. No negative-stranded RNA was found. It was also shown that most of the MHV strains had diverged quite extensively in their genetic sequences. However, MHV-3, a hepatotropic strain, and A59, a nonpathogenic strain, were found to have very similar oligonucleotide fingerprinting patterns. Yet, each of them contained two to four specific oligonucleotides. The MHV-3-specific oligonucleotides were conserved in almost all of the hepatotropic MHV strains studied. In contrast, two of the A59-specific oligonucleotides were absent from the genomes of all hepatotropic strains. These findings suggest that these unique oligonucleotides might be localized at the genetic region(s) associated with viral pathogenicity or other biological properties of the virus. Comparison of viral structural proteins also suggests that MHV-3 and A59 are more closely related than other MHV strains. The significance of these findings is discussed.